Fatores associados ao comportamento de grazing em candidatos à cirurgia bariátrica atendidos em um hospital público de referência em Belém-Pa. - COSTA, Ana Paula da Silva (2023)
Introduction: Grazing behavior occurs when there is a repeated ingestion of small amounts of food with a frequency of more than twice, in an unplanned way, being subdivided into compulsive and non-compulsive grazing. It is an emerging behavioral phenomenon today, which may contribute to the failure of bariatric surgery. Objective: To analyze the grazing behavior and associated factors in candidates for bariatric surgery treated at a hospital in Belém-PA. Methodology: Cross-sectional, descriptive and analytical study, carried out with candidates for bariatric surgery followed up in a public hospital in Belém-PA. Socioeconomic, clinical and physical activity data were given. The classification of obesity was performed by assessing weight and height using a platform type scale. For the evaluation of grazing behavior, the Rep(eat) (Repetitive E Questionnaire), Brazilian version, was applied. Results: There were 75 participants, of which 92% were women with a mean age of 34.9±9 years. It was found that 58.7% of the participants had non-compulsive grazing. Participants who practiced physical activity in the last 3 months were considered statistically lower for compulsive grazing (p=0.007) and non-compulsive grazing (p=0.028). Participants who used weight-loss drugs in the last 3 months presented statistically lower rates for compulsive grazing (p=0.004) and non-compulsive grazing (p=0.004). Conclusion: The identification of grazing behavior must be performed early during the preoperative period, which must be trimmed by the multidisciplinary team. In addition, they are public policies aimed at comprehensive care for candidates for bariatric surgery.